PENGARUH KEPUASAN KERJA TERHADAP PERILAKU ORGANIZATIONAL CITIZENSHIP BEHAVIOUR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI PADA KARYAWAN ADMINISTRATIF DI LINGKUNGAN UNIVERSITAS WIJAYA KUSUMA SURABAYA) - Mrs Kristiningsih; Dewi Nuraini (BALANCE: Economic, Business, Management and Accounting Journal, 2017)
ABSTRACT  This study aims to examine the effect of job satisfaction on organizational citizenship behavior with affective commitment as a mediating variable. The research took the case to the administrative employees at Wijaya Kusuma University Surabaya.This research uses purposive simple random sampling where the respondent is selected with criterion: has been working in UWKS for one year or more than one year.There are 13 existing departments including administrationbureauand administration of the faculty. From the 150 respondents elected, it was only 117 questionnaires that are eligible for processing. The analytical technique used in this research  is Structural Equation Model by using AMOS ver 16 program statistic.From the nineteen job satisfaction indicators only nine are valid and reliable, while the five indicators for OCB are valid and reliable. Likewise seven indicators for commitment are valid and reliable.  The result of the research shows that job satisfaction has a direct effect on affective commitment. While Commitment has no significant effect on OCB, likewise Job satisfaction has no direct effect on OCB. So Commitment is not a mediating variable that connects between the job satisfaction and OCB.Keyword : Job satisfaction, affective commitment, organizational citizenship behaviourCorrespondence to : kristiningsih_uwks@yahoo.co.id